(untitled) (The Peerian Journal, 2025)
This article provides a comprehensive conceptual analysis of the central theme in Sufi philosophy - the issue of human nature - from a philosophical and ideological perspective. In Sufism, a human being is interpreted as a perfect creature embodying the essence of the universe, having found balance between the external and internal, material and spiritual aspects. The article extensively covers the conceptual approach to human essence, emphasizing that in Sufism, the attainment of human perfection is not only through personal effort but also involves traversing a spiritual distance connected with divine light. In Sufism, this process occurs through "suluk" - the journey of entering the spiritual path and receiving education under the guidance of a mentor (pir).